INOVASI PENGEMBANGAN KAWASAN WISATA BERKELANJUTAN DI OBJEK WISATA ALAM SAWAH LUKIS LEMBANG RANDANAN, KECAMATAN MENGKENDEK, KABUPATEN TANA TORAJA - Damayanti, Irene Devi; Mantong, Agustinus; Kudu, Jian (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTThe tourism sector is an important component in economic development which is developed as a source of income for a region. Comparative studies from several tourist areas show that cleanliness, adequate infrastructure, availability of appropriate facilities, and collaboration between the government, private sector and community are the keys to success. The existence of Lembang Randanan as a tourist village offers various tourist objects that can be visited, one of which is Sawah Lukis. One of the tourist attractions in Lembang Randanan is the Painted Rice Fields. The fertile rice fields provide beautiful landscapes and a deep impression. The author, as a KKN-T student class XLIII UKI Toraja with the theme Tourism Area Development Innovation, together with Lembang officials and the community, innovated to develop and promote this tourist attraction which has not been managed well. This service is carried out using a qualitative descriptive method to describe facts and phenomena related to the basic principles of innovating the development of tourist areas. The results achieved from this service include increased cleanliness and tidiness as well as the availability of facilities and infrastructure that support the development of the Sawah Lukis tourist attraction, such as trash cans, decorative lights, painting halls and gazebos. Based on the results that have been achieved, the dedication to develop the Sawah Lukis Tourism area has been carried out well. It is hoped that this service will become a reference for the community to continue to manage the tourist area in Lembang Randanan optimally.Keywords: development innovation, natural tourism, management, promotion, painted rice field. ABSTRAKSektor pariwisata menjadi salah satu komponen penting dalam pembangunan ekonomi yang dikembangkan sebagai salah satu sumber pendapatan suatu daerah. Studi banding dari beberapa kawasan wisata menunjukkan bahwa kebersihan, infrastruktur yang memadai, ketersediaan fasilitas yang layak, serta kolaborasi antara pemerintah, sektor swasta, dan masyarakat adalah kunci keberhasilan. Keberadaan Lembang Randanan sebagai salah satu desa wisata menawarkan berbagai objek-objek wisata yang dapat dikunjungi salah satunya adalah Sawah Lukis. Salah satu wisata yang ada di Lembang Randanan adalah Sawah Lukis. Sawah yang subur memberikan lanskap (pemandangan) yang cantik dan kesan yang mendalam. Penulis selaku mahasiswa KKN-T angkatan XLIII UKI Toraja dengan tema Inovasi Pengembangan Kawasan Wisata bersama aparat lembang dan masyarakat melakukan inovasi untuk mengembangkan dan melakukan promosi objek wisata yang belum dikelola dengan baik ini. Pengabdian ini dilakukan dengan metode deskriptif kualitatif untuk menggambarkan fakta dan fenomena yang terkait dengan prinsip dasar melakukan inovasi pengembangan kawasan wisata. Adapun hasil yang dicapai dari pengabdian ini antara lain peningkatan kebersihan dan kerapian serta tersedianya sarana dan prasarana yang mendukung pengembangan Objek Wisata Sawah Lukis seperti tempat sampah, lampu hias, pengecatan aula dan gazebo. Berdasarkan hasil yang telah dicapai, pengabdian untuk mengembangkan kawasan Wisata Sawah Lukis ini sudah telaksana dengan baik. Pengabdian ini diharapkan menjadi acuan masyarakat untuk terus mengelola kawasan wisata di Lembang Randanan dengan maksimal.Kata Kunci: inovasi pengembangan, wisata alam, pengelolaan, promosi, sawah Lukis.